Students’ perception of the role and challenges of practical in understanding clothing and textiles concepts - Juliana Ego Azonuche; Chukwudi Ogwu; Fidelis Ifeakachuku Achuba (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
The importance of laboratory works in the training of vocational students cannot be underestimated. The aim of this investigation was to explore the challenges faced by clothing and textiles students in the course of laboratory works.The investigation employed a cross-sectional survey involving students taking clothing and textiles in tertiary institutions in Delta State Nigeria which served as respondents. Data collection was done using a self-developed questionnaire administered through personal contacts. Data collected were analyzed using the mean and standard deviation. The benchmark for accepting or rejecting statements made in the questionnaire was set 2.50. The study established positive disposition of clothing and textiles students towards the role of laboratory works. This hinged on the overall relevance of laboratory works in explaining key concepts in clothing and textiles curriculum. It equally provided insight on the perceived challenges. It is therefore concluded that laboratory works should be sustained since it enhances students understanding of curriculum concepts.